Heat Stress in Legume Seed Setting: Effects, Causes, and Future Prospects - Liu, Yonghua; Li, Jiajia; Zhu, Yulei; Jones, Ashley; Rose, Ray J.; Song, Youhong (Frontiers in Plant Science, 2019)
Grain legumes provide a rich resource of plant nutrition to human diets and are vital for food security and sustainable cropping. Heat stress during flowering has a detrimental effect on legume seed yield, mainly due to irreversible loss of seed number. To start with, we provide an overview of the developmental and physiological basis of controlling seed setting in response to heat stress. It is shown that every single process of seed setting including male and female gametophyte development, fertilization, and early seed/fruit development is sensitive to heat stress, in particular male reproductive development in legume crops is especially susceptible. A series of physiochemical processes including heat shock proteins, antioxidants, metabolites, and hormones centered with sugar starvation are proposed to play a key role in regulating legume seed setting in response to heat stress. The exploration of the molecular mechanisms underlying reproductive heat tolerance is in its infancy. Medicago truncatula, with a small diploid genome, and well-established transformation system and molecular platforms, has become a valuable model for testing gene function that can be applied to advance the physiological and molecular understanding of legume reproductive heat tolerance.